# Changes

<math>\frac{\partial M}{\partial y} = \frac{\partial N}{\partial t}</math>

To find the solution of this equation, we assume that the solution is φ = constant. We can re-write a different form of this equation by substituting <math>\frac{\partial \phi}{\partial t} = M</math> and <math>\frac{\partial \phi}{\partial y} = N</math>. This yields <math>(\frac{\partial \phi}{\partial t}) dt + (\frac{\partial \phi}{\partial y}) dy = 0</math>~~, which makes sense~~.

Go through the example to find φ by integrating, then check that